Association of Superoxide Dismutase with Ticagrelor Treatment in Patients with Peripheral Arterial Disease - Fakhri, Yasameen Ali; Al-Ani, Ali Waleed (Iraqi Journal of Science, 2025)
Peripheral artery disease (PAD) is associated with increased oxidative stress and impaired endothelial function. Ticagrelor treatment improves antioxidant properties in addition to its antiplatelet effects. This study investigated the impact of Ticagrelor treatment on serum superoxide dismutase (SOD) levels and other biochemical parameters in PAD patients. It also evaluated the potential diagnostic accuracy and clinical utility of specific biomarkers based on receiver operating characteristic (ROC) analysis. Seventy individuals were categorized into healthy control (n=40), baseline PAD patients not on Ticagrelor (B-PAD, n=30), and same PAD patients after treated with Ticagrelor (A-PAD, n=30). Parameters measured included SOD concentration/activity, oxidized protein levels, serum trace elements, and other biochemical parameters. PAD patients showed elevated oxidized protein level and reduced SOD concentration and activity versus control group. Ticagrelor improved antioxidant status in PAD via SOD upregulation and reduced protein oxidation. Parameters of oxidative stress/antioxidants exhibited potential for PAD screening, diagnosis and longitudinal monitoring of treatment response using the diagnostic metrics derived from ROC analysis.